Cavernous lymphangioma of the digits: a rare cause of macrodactyly - Leong, JF; Levin KB,; Rajkumar V,; Abdullah S,; Jamari Sapuan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Cavernous lymphangioma is a congenital malformation of lymphatic system causing dilated lymphatic sinuses that involve the skin and subcutaneous tissues. This was an interesting case of dystrophic macrodactyly of the left ring and little finger in a 18-month-old girl who presented with swollen and sausage like fingers deformity which turned out to be an isolated cavernous lymphangioma. This tumor, although rare to occur in the extremeties, must be differentiated from other congenital vascular lesions of the hand that include arteriovenous malformations and hemangiomas. Diagnosis should be solely based on histopathological analysis of the excised tissue mass. Surgical excision is usually necessary for satisfactory functional and cosmetic outcome.